2020
DOI: 10.1021/acsanm.9b02590
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Graphitic Carbon Nitride Nanosheets for Photocatalytic Hydrogen Evolution

Abstract: Among semiconductor photocatalysts, graphite carbon nitride (g-C 3 N 4 ) has caused great concern in terms of water splitting. Here, we prepared ultrathin g-C 3 N 4 nanosheets with high photocatalytic activity by recrystallization of urea from N,Ndimethylformamide (DMF) to form a hydrogen-bonding network (named as UDF) and then utilized the as-prepared complex for the synthesis of carbon nitride. Single-crystal Xray diffraction showed that urea and DMF form a 3:1 solvate in the UDF precursor, which manifests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 59 publications
2
42
0
Order By: Relevance
“…Notice that appreciable HER was gained also with no metal, underlining the potentiality of such photoactive material. This evidence corroborates a photoreaction mechanism typical of the photocatalytic systems for H 2 production from water [1,3,23], wherein:…”
Section: Further Investigation Of Dmasnbr 3 /G-c 3 Nsupporting
confidence: 85%
See 1 more Smart Citation
“…Notice that appreciable HER was gained also with no metal, underlining the potentiality of such photoactive material. This evidence corroborates a photoreaction mechanism typical of the photocatalytic systems for H 2 production from water [1,3,23], wherein:…”
Section: Further Investigation Of Dmasnbr 3 /G-c 3 Nsupporting
confidence: 85%
“…Since Pt is in situ photodeposited on the catalyst surface, after Ar bubbling, a small volume from an H 2 PtCl 6 aqueous solution (0.15, 3 or 15 g L −1 ) was added using a 10-100 µL micropipette to the catalyst suspension, directly in the photoreactor. This was closed with sleeve stopper septa and was irradiated, as described in the following, achieving simultaneous Pt deposition and H 2 production [23,[28][29][30]. Irradiation was done under simulated solar light using a Solar Box 1500e (CO.FO.ME.GRA S.r.l., Milan, Italy) set at a power factor of 500 W m -2 , and equipped with UV outdoor filter made of IR-treated soda lime glass.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, reports have shown that ultrathin g-C 3 N 4 nanolayers are able to greatly enhance photocatalytic hydrogen evolution. 13 , 14 Porous conjugated polymers as photocatalysts have been rapidly developed in recent years, and the structures of the polymer have been proven to be one of the key factors for obtaining good performance. 12 25 Making the linear conjugated polymer particles as small as possible can shorten the required distance for exciton diffusion to suppress the unwanted annihilation of excitons as well as increase the catalytic surface area, therefore enhancing the photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Modied g-C 3 N 4 with nanotubes, nanosheets and porous structures have been successfully prepared by methods including the hard template method, so template method, acid treatment method and thermal etching method. 20,21 However, these methods suffer from drawbacks such as template removal, residual impurities, consumption of strong acids and low efficiency. 22,23 Therefore, it is still an urgent task to explore facile and highly-efficient methods for the nanostructure engineering of g-C 3 N 4.…”
Section: Introductionmentioning
confidence: 99%